2016
DOI: 10.1371/journal.pone.0167259
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Recreation on Animals Revealed as Widespread through a Global Systematic Review

Abstract: Outdoor recreation is typically assumed to be compatible with biodiversity conservation and is permitted in most protected areas worldwide. However, increasing numbers of studies are discovering negative effects of recreation on animals. We conducted a systematic review of the scientific literature and analyzed 274 articles on the effects of non-consumptive recreation on animals, across all geographic areas, taxonomic groups, and recreation activities. We quantified trends in publication rates and outlets, ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
198
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 207 publications
(204 citation statements)
references
References 82 publications
(96 reference statements)
5
198
0
1
Order By: Relevance
“…, Larson et al. ). The most commonly reported wildlife responses to recreation are behavioral and physiological, including elevated stress hormones and avoidance or displacement from areas of disturbance (Harris et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…, Larson et al. ). The most commonly reported wildlife responses to recreation are behavioral and physiological, including elevated stress hormones and avoidance or displacement from areas of disturbance (Harris et al.…”
Section: Introductionmentioning
confidence: 99%
“…Although useful, many of the previous studies assessing the effects of winter recreation on wildlife have been limited spatially and temporally, and most were focused within a single study area and on a single form of winter recreation (Larson et al. ). As backcountry winter recreation grows in intensity and spatial extent, coupled with the potential concentration of activities due to climate change‐driven reductions in snow area and season (Dawson et al.…”
Section: Introductionmentioning
confidence: 99%
“…, Larson et al. ). Winter sports are particularly invasive to sensitive wildlife due to the noise and speed associated with snowmobilers and backcountry skiers (i.e., off‐piste skiers; Braunisch et al.…”
Section: Introductionmentioning
confidence: 99%
“…While recreational use of an area is generally assumed to be more compatible with species' conservation than consumptive activities such as development or resource extraction, animals' perceived risk from recreation can lead to behavioral tradeoffs such as increased vigilance and decreased feeding, mating, or parental care activities (Frid & Dill, 2002;Larson, Reed, Merenlender, & Crooks, 2016). Snow-based recreation may also have a greater negative affect on wildlife compared to aquatic or summer-terrestrial sports (Larson et al, 2016), with changes in space or temporal use of an area frequently observed. Moose (Alces alces) and mountain caribou (Rangifer tarandus caribou), for example, were spatially displaced from suitable habitat by the presence of snowmobile recreation (Harris, Nielson, Rinaldi, & Lohuis, 2013;Seip, Johnson, & Watts, 2007), while mountain goats (Oreamnos americanus ;Richard & CĂŽtĂ©, 2016) and black grouse (Tetrao tetrix) avoided developed ski areas (Patthey, Wirthner, Signorell, & Arlettaz, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Developed ski resorts, which include considerable infrastructure, tree removal, and continuous maintenance (Rixen & Rolando, 2013), also differ from dispersed recreation, which requires little infrastructure and minimally affects existing forest conditions. The number of participants and total days spent on winter recreation is projected to increase over the next several decades (White et al, 2016), and coupled with the potential of climate-induced reduction in persistent and deep snow, research is needed to characterize the effects of winter recreation on endangered or threatened species that are snow-associated (Larson et al, 2016). Canada lynx (Lynx canadensis), a threatened species in the continental United States, is of particular concern because of its relative rarity as well as its adaptation to and reliance on deep snow to limit competition from other predators during winter (Buskirk, Ruggiero, & Krebs, 1999).…”
Section: Introductionmentioning
confidence: 99%